Impact of Service Quality on Destination Image of Lake Buyan with Tourist Satisfaction as an Intervening Variable - Wisnawa, I Made Bayu (Jurnal Manajemen Pelayanan Hotel, 2024)
The study aims to examine the impact of the quality of service on the image of Lake Buyan's destination with tourist satisfaction as a mediator variable. The study uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The sample of this study consisted of 150 tourists who visited Lake Buyan. Data collection is carried out through surveys using questionnaires designed to measure travelers' perceptions of the quality of service, tourist satisfaction, and destination image. The results of the analysis show that the quality of the service has a significant influence on tourist satisfaction and the image of the destination. Tourist satisfaction proved to be a full mediation in the relationship between the quality of service and the image of the destination. The findings confirm that improved quality of services in Lake Buyan can increase tourist satisfaction, which in turn reinforces the positive image of this destination. The study provides practical implications for tourist destination managers and stakeholders in Lake buyan to improve the quality of service as a strategy in promoting a positive destination image through improved client satisfaction. The research also offers new insights to researchers and practitioners in the field of tourism management and destination marketing. Keywords: Service Quality, Tourist Satisfaction, Destination Image